Evaluation Of The Implementation Of The Pramuka School Extracurricular Program - Tyas, Veronica; Elianasari, Elianasari; Zulaikha, Siti (International Journal of Elementary Education, 2021)
The research objective was to determine the Pramuka extracurricular program's implementation by analyzing students' reactions to the implementation of Pramuka activities, analyzing programs, changes, and the final achievement of the Pramuka extracurricular education program. This research was conducted from April to December 2020 at SD Strada Bhakti Utama, South Jakarta. This research's type of evaluation is evaluation research with the CIPP model (Context, Input, Process, and Product). Research methods use a combination of quantitative methods and qualitative methods to be used together. Researchers used the purposive sampling technique for sampling where the source of information was the principal, teacher guidance, and students in grades V and VI who were actively involved in Pramuka. Data collection techniques through interviews, documentation study, and observation. The data is taken qualitatively. The results showed that Pramuka activities carried out character building followed the goals and expected outcomes, including students becoming more active in learning, more patient, more focused, more sensitive, more appreciative of friendship, increased knowledge, more empathetic, and life thrifty.